Psychotropic Medication Use and Perceptions of Medication Effects Among Transition-Age Foster Youth. - Park, Keunhye; Okpych, Nathanael J.; Courtney, Mark E. (Child & Adolescent Social Work Journal, 2019)
The prevalence of psychotropic medication use among children and adolescents in foster care has received increasing attention from policymakers and scholars and led to responses from government. Most research has focused on school-age foster children; less is known about psychotropic medication use among foster youth transitioning to adulthood from care. Using data from a longitudinal study of transition-age foster youth (n = 611), this study examines the prevalence of psychotropic medication use over time, evaluates youths' perceptions of the benefits of medication, and assesses associations between medication use and behavioral health problems. The overall rate of psychotropic medication use dropped from age 17 to age 19. Among youth with at least one behavioral health problem, rates of psychotropic medication use also declined over time. Decreases in psychotropic medication use between age 17 and 19 were found among youth with the following disorders: mania, an alcohol use disorder, and a non-alcohol drug use disorder. Behavioral health status and youths' living arrangements were associated with the likelihood of psychotropic medication use at age 17, whereas only behavioral health status was associated with the likelihood of psychotropic medication use at age 19. Most youth reported either a positive or neutral view of the relative benefits of using medications. Among youths who had used medications, those in relative foster homes were less likely than those in non-relative foster homes to report negative views of their medications. The findings have implications for child welfare and health care professionals and policymakers.